Sources: notable selections in marriage and the family - DelCampo, Robert; DelCampo, Diana (New Jersey: Dushkin/McGraw Hill, Inc., 1999)
Contents : Definitions of the family,the marriages of marriage,the family as a unity of interacting personalities,the universality of the family: a conceptual analysis,journal of marriage and the family,the general systems approach to the family,premarital relationships,i believe that we need two types of marriage,theories of mate selection
Incluye bibliografía
Keywords: Familia - Matrimonio